Предмет: Алгебра,
автор: BlueVelvet
СРОЧНО! СОКРАТИТЕ ДРОБЬ
Ответы
Автор ответа:
0
(х² + у² - z² + 2xy)/(x² - y² + z² + 2xz) =
= ((х² + у² + 2xy) - z² )/((x² + z² + 2xz) - y² ) =
= ((х + у)² - z² )/((x + z)² - y² ) =
=(x + y + z)(x + y - z)/(x + y + z)(x - y + z)) =
= (x + y - z)/(x - y + z)
= ((х² + у² + 2xy) - z² )/((x² + z² + 2xz) - y² ) =
= ((х + у)² - z² )/((x + z)² - y² ) =
=(x + y + z)(x + y - z)/(x + y + z)(x - y + z)) =
= (x + y - z)/(x - y + z)
Похожие вопросы
Предмет: Русский язык,
автор: irinaSD85
Предмет: Русский язык,
автор: иринаБ1987
Предмет: Қазақ тiлi,
автор: Amir2019
Предмет: Математика,
автор: Dimamikheev666
Предмет: Математика,
автор: ilyaCreative